(untitled) (Journal Of Educational and Psychological Researches, 2018)
The study aims to examine the emotional innovation, constructive thinking, foresight, and meditation among university students. Besides, attempts to explore the relationship between emotional innovation and constructive thinking, the relationship between emotional innovation and foresight, and meditation, the relationship between constructive thinking and foresight, and meditation, finally, the relationship among emotional innovation, constructive thinking, foresight, and meditation of university students regarding the variables of gender and major. A total of (400) students were selected as a sample for the study. The results revealed that university students have a high level of emotional innovation that induce them to take positive role in social activities that meet their needs as well as they have significant levels of constructive thinking, foresight, and meditation. The results also showed there is no a significant relationship among emotional innovation, constructive thinking, foresight, and meditation